Comparison of MMR Vaccine V/S 5-Fluorouracil in Treatment of Palmo-plantar Warts - Saira Rafique, Tahir Hassan, Muhammad Khurram Shahzad, Nazia Hanif, Sarwar Rafique, Sumaira Rafique (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Human papilloma virus is a large group of DNA containing viruses that infect squamous epithelium of skin or uncornified mucous membrane. Aim: To compare the outcomes of MMR vaccine V/S 5 fluorouracil in treatment of palmo-plantar warts in patients among male and female patients. Study Design: Experimental study. Methodology: In order to collect the data, simple random sampling technique was used. Enrolled patients (n=102) were divided into two groups. Group-A received intra-lesional MMR vaccine (0.1-0.5mal) while other group received intra-lesional 5-Fluorouracil (0.1-0.5mal) injection. Both groups received intra-lesional injections in warts at 2 weekly interval for 3 months. SPSS v 23 evaluated data. Chi-square test was used to compare the gender distribution, results, responder and recurrence between both groups with p-value less than 0.05 as significant. Results: Mean age of the patients of group A was 30.5 ± 6.0 and the mean age of patients of group B was 28.2 ± 8.7 years. In Group A, 33 patients (58.9%) were responders, while in Group B, 43 patients (76.8%) were responders. P-value (0.043) suggested that the difference in response rate between the two groups was statistically significant. Practical Implication: This study compared the efficacy of two different treatment options that were commonly used in palmo-planter warts management. Secondly, it added to local literature regarding their efficacy in comparison to each-other. Conclusion: It was concluded that intra-lesional 5-FU was more safe and effective treatment in comparison to injection MMR for palmo-planter warts as it showed high response rate with low recurrence. Keywords: Efficacy, MMR Vaccine, Response Rate, 5-Flourouracil and Intra-lesional Injection.